The Refugee Crisis On Twitter: A Diversity Of Discourses At A European Crossroads - Gualda, Estrella; Rebollo, Carolina (Journal of Tourism, Sustainability and Well-being, 2016)
In the last decade, the European Union has approved and launched measures to promote Intercultural Cities, Diversity Management and the Integration of Immigrants in Europe. Despite this European framework, we are now at a crossroads between solidarity and humanity and an important restriction of refugees’ human rights across Europe. In this paper, we try to compare the international approaches to the refugee crisis in different countries in Europe. Data were extracted from Twitter. We obtained thousands of tweets about “refugees”, using this word in six different languages (English, French, German, Italian, Portuguese, and Spanish) from end November 2015 to 27 February 2016 as search strings. We performed a discourse analysis, focusing on the comparison between countries. A qualitative analysis with the help of both Atlas ti and T-Lab software was performed. The results showed a diversity of current discourses in Europe about refugees and the refugee crisis (from solidary to xenophobic ones), some of them very characteristic of particular countries or of local events experienced in these countries. These results allow us to reinforce the idea that we are at a key moment for the future development of Europe, especially regarding aspects concerning living together in cities and villages.